Family therapy with children - Zevallos, Roxana (2001)
The analysis of the family therapy field has shown a particular interest in acknowledging that the children´s experiences, specially their disorder, are related to their family situation. Unlike individual therapy, which is approached differently, the systemic patterns focuses on the interaction between parents and emphasizes their ability to reach contracts which benefit the best emotional and psychological development of their children. This means that the family therapist may arrange for sessions so that parents and children meet in the same place. Thus, family therapists must be prepared to work with children.